2010
DOI: 10.1111/j.1747-4477.2010.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activities of chlorhexidine gluconate, sodium hypochlorite and octenidine hydrochloride in vitro

Abstract: The objective of this study was to compare the antimicrobial activity of sodium hypochlorite (NaOCl), chlorhexidine gluconate (CHX) and octenidine hydrochloride (OCT) in different concentrations against endodontic pathogens in vitro. Agar diffusion procedure was used to determine the antimicrobial activity of the tested materials. Enterococcus faecalis, Candida albicans and the mixture of these were used for this study. In the agar diffusion test, 5.25% NaOCl exhibited better antimicrobial effect than the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
2
31
0
5
Order By: Relevance
“…21 Therefore, antimicrobial agents, such as octenidine dihydrochloride (OCT) and polyhexamethylene biguanide (PHMB) have been investigated as alternatives to CHX because of their superior microbicidal activity and lower cytotoxicity than CHX. 22,23,24,25 OCT is an antiseptic agent recently used for the management of skin burns, wounds, and as a mouth rinse. OCT belongs to the bipyridines, carrying two cationic active centers per molecule, and demonstrates the broad-spectrum antimicrobial effects on both gram-positive and gram-negative bacteria, fungi, and several viral species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Therefore, antimicrobial agents, such as octenidine dihydrochloride (OCT) and polyhexamethylene biguanide (PHMB) have been investigated as alternatives to CHX because of their superior microbicidal activity and lower cytotoxicity than CHX. 22,23,24,25 OCT is an antiseptic agent recently used for the management of skin burns, wounds, and as a mouth rinse. OCT belongs to the bipyridines, carrying two cationic active centers per molecule, and demonstrates the broad-spectrum antimicrobial effects on both gram-positive and gram-negative bacteria, fungi, and several viral species.…”
mentioning
confidence: 99%
“…Previous studies have shown that the efficacy of OCT against dental plaque-associated bacteria (e.g., S. mutans and A. viscosus) was comparable to that of CHX. 24,27 PHMB is a type of modern antiseptic that combines a broad antimicrobial spectrum with low toxicity, high tissue compatibility, no reported adsorption, and is used as a solution, gel, ointment, or foam. As such, it is one of the most promising antiseptic substances.…”
mentioning
confidence: 99%
“…Agar difüzyon metodunda mikrobiyal inhibisyon zonunun oluşması, test edilen maddenin çözünürlüğü ve agar içerisine diffüze olabilme yeteneğine bağlıdır. 18 Dentin ve dentin komponentlerinin kök kanal medikamentlerinin antimikrobiyal etkinliğini inhibe ettiği 19 düşünüldüğünde dentin blok modelinin bu çalışma için daha uygun olduğu görülmektedir.…”
Section: Discussionunclassified
“…Mixing OCT with calcium hydroxide significantly increased the antibacterial effect of Octenisept ® , but did not alter its antifungal activity, unlike in regards to the use of CHX alone, which yielded a higher antibacterial and antifungal efficiency compared to that of its combined version with Ca(OH) 2 [35]. Tirali et al [36] made a study to compare the antimicrobial efficiency of various endodontic irrigants including NaOCl, CHX and OCT in different concentrations on selected root canal microorganisms like E. f aecalis, C. albicans and a mixture of them both. The results of this study indicated that various concentrations of octenidine dihydrochloride were as effective as a 5.25% solution on the tested microorganisms, and the inhibition zones observed with CHX 2% and 1% groups were significantly less than NaOCl and octenidine.…”
Section: Octenidine -Octmentioning
confidence: 99%